Immersive Learning through Virtual Reality: A New Paradigm in Chemical Engineering Education - Bello, Usman; Wan Osman, Wan Nur Aisyah; Samsuri, Shafirah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Traditional chemical engineering education faces persistent challenges, as lecture-based instruction and limited laboratory access restrict students’ engagement, practical skill development, and comprehension of complex engineering concepts. In overcoming these challenges, immersive virtual reality (VR) learning environments are increasingly being adopted to enhance students’ visualization, interactivity, and experiential learning. Therefore, this study aims to explore how VR can transform chemical engineering education by enhancing student engagement, conceptual understanding, and practical learning experiences. This review also analyzed and mapped research trends in the application of VR for immersive learning in chemical engineering education using keywords like ''Immersive Learning'', ''Virtual Reality'', ''Chemical Engineering'' and ''Chemical Engineering Education''. Accordingly, the keyword co-occurrence analysis revealed four thematic clusters linked to immersive visualisation, collaborative VR learning, VR–AI integration, and safety-oriented training. Based on these findings, a four-stage curriculum integration model is proposed (pre-conceptual familiarisation - immersive experimentation - hybrid transfer - real-lab validation). A comparative cost analysis indicates that although VR-based learning demands a higher upfront investment, it achieves cost parity within approximately 1.5 years and reduces total training expenses by about 40–45% in the third year, offering greater economic advantage for larger student cohorts. Finally, the synthesis indicates that VR can enhance conceptual understanding, hazard-awareness, and systems-level reasoning while improving utilisation efficiency in laboratory-intensive programmes. Future research should prioritise controlled cohort comparisons and longitudinal verification of transferability to physical plant behaviour.